Brain‐bladder control network: The unsolved 21st century urological mystery. (17th February 2015) - Kitta, Takeya; Mitsui, Takahiko; Kanno, Yukiko; Chiba, Hiroki; Moriya, Kimihiko; Shinohara, Nobuo
Abstract A review of functional brain imaging studies of bladder control in participants with normal control and pathological conditions. In the normal condition, bladder and urethral afferents received in the periaqueductal gray relay the information to the insula, the anterior cingulate cortex and the prefrontal cortex. During the storage phase, these superior regions control the pontine micturition center to inhibit voiding. In overactive bladder patients, brain responses are different. Cortical responses become exaggerated, especially in the anterior cingulate cortex and the supplementary motor area. That is what presumably evokes the "urgency". The supplementary motor area is activated during contraction of the pelvic floor muscles, and provides protection against incontinence. We believe that functional brain imaging studies are promising not only for the understanding of bladder dysfunction, but also as an aid to the development of therapeutic options for chronic disorders.